Gender differences among drug abusers in the process of readiness to change - Ibrahim, Fauziah; Ab. Rahman, Roseliza Murni; Jusoff, Kamaruzaman; Wan Sulaiman, Wan Shahrazad; Mohamad, Lukman @ Zawawi; Zainal, Arifin; Ahmad Zamani, Zainah (IDOSI Publications, 2011)
Although gender-related issues are often cited as playing an important part in determining patterns of illicit drug use, little is known about the differences between men and women drug users within treatment settings. This article is provided to measure gender differences in terms of readiness to change among rehabilitees of Malaysian National Narcotics Rehabilitation Centre (PUSPEN) via the stages of Change Readiness and Treatment Eagerness Scale (SOCRATES). A total of 609 people consisting of 490 men and 109 women drug users from six drug rehabilitation centers in Peninsular Malaysia responded to a survey by using stratified random sampling and systematic random sampling. Data were analyzed using t-test analysis to compare the readiness to change among men and women rehabilitees in terms of recognition, ambivalence and taking steps. The results of the study showed significant differences between gender in terms of taking steps, however no significant differences were noted in the dimensions of recognition and ambivalence. Input to the identification of changes associated with readiness to change among gender would be able to provide a new data to formulate more effective strategies for rehabilitated drug addicts among the gender.